1985
DOI: 10.1016/s0022-5347(17)47339-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy: One Stage or Two?

Abstract: Two hundred and fifty cases of percutaneous nephrolithotomy (PNL) are described. One hundred and fifty cases were treated in two stages, 100 in a single stage. The one-stage method has been shown to be as safe as the two-stage method but should be reserved for those with experience of the technique and who possess adequate instrumentation. PNL has proved to be a preferable option to open stone surgery and a useful alternative to extracorporeal shock wave lithotripsy (ESWL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 1 publication
1
46
0
2
Order By: Relevance
“…7,8,15,16 In our experience, avoiding a nephrostomy tube is feasible in patients with upper calyceal or supracostal access, without increasing pulmonary morbidity. None of our patients who underwent totally tubeless PCNL with supracostal access developed any pulmonary complications.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…7,8,15,16 In our experience, avoiding a nephrostomy tube is feasible in patients with upper calyceal or supracostal access, without increasing pulmonary morbidity. None of our patients who underwent totally tubeless PCNL with supracostal access developed any pulmonary complications.…”
Section: Discussionmentioning
confidence: 73%
“…In 1984, Wickham et al 8 reported their experience with percutaneous stone extraction and stated that in selected cases it is not unreasonable to avoid leaving a nephrostomy tube. However, in 1986, Winfield et al 9 reported prolonged hospitalization and pain in two patients after percutaneous stone removal when nephrostomy tubes were not left in place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aslında Wickham ve arkadaşları, ilk kez tek aşamalı PNL işlemini 1984 yılında bildirmiş ve bu işlem tüpsüz olarak gerçekleştirilmiştir [9]. Bu ça-lışmada ameliyat ettikleri 100 hastada ne internal ne de eksternal tüp kullanmadıklarını bildirmişlerdir, ayrıca ortalama hastanede kalış süresini de 2.8 gün olarak rapor etmişlerdir.…”
Section: Discussionunclassified
“…15, 3, 16, 17 Repor -ted benefits of the tubeless approach include reduced admission durations, lower analgesia requirements, faster time to return to normal activities, and lower cost. 14, 18 The present study compares tubeless percutaneous nephrolithotomy with conventional percutaneous nephrolithotomy in regard to postoperative outcome, complications and safety.…”
Section: -13mentioning
confidence: 99%